Eksplorasi Minyak Republik Rakyat Tiongkok (RRT) Di Reed Bank Dan Dampaknya Bagi Kedaulatan Filipina - Mioldry Evilyn Saleky; Josina Augustina Yvonne Wattimena; Dyah Ridhul Airin Daties (Faculty of Law Pattimura University, 2022)
Introductioan: Oil exploration carried out by the people’s Republic of china at the reed bank. China is based on the nine dash line, but the philippnes claims that the reed bank is its territory based on the UNCLOS 1982.Purposes of the Research: This paper aims to determine and analyze the impact of oli exploration in the reed bank with the sovereignty of the Philippines. Methods of the Research: The research method in this writing uses the type of analytical prescriptive research. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques. Results of the Research: The results obtained are to axplain that the impact of oil exploration in the reed bank by the RRT on the Philippines is not yet real yet, but with the action of oli exploration in the reed bank that continues to be carried out by the RRT, it will pose a threar to the sovereignty of the Philippines in the future.